Penyuluhan Pola Hidup Sehat dan Dampak Bullying Terhadap Kesehatan Mental di Sekolah MI Muhammadiyah Barengkok - Rai Sara Purnama Sari; Nadhya Salwa Nur Arraafi’a; Maya Rosmita (Literasi Nusantara Publisher, 2023)
The problem of public awareness in Indonesia to lead a healthy lifestyle is still relatively low, unhealthy lifestyles and modern lifestyles cause various health problems that can cause various diseases and physical problems. In addition to physical health, mental health also needs to be considered, bullying has an impact on mental health for victims. Bullying is an act that is carried out by hurting physically, verbally or psychologically by a person or group who feels stronger to a victim who is weaker physically or mentally repeatedly without resistance with the aim of making people suffer. The implementation method is carried out directly by providing counselling and providing basic materials on healthy lifestyles and the impact of bullying at the MI Muhammadiyah Barengkok school in Bogor. The results of this service aim to educate students to apply a healthy lifestyle in daily activities and avoid bullying and also from bullying in the school environment and in the community. In conclusion, through the implementation of this activity, students get briefing on maintaining a healthy lifestyle and preventing bullying in the school environment and in the community. With this activity so that it can help students as the younger generation create prosperity for themselves, their parents, and the community.